A 13‐year retrospective study evaluating the efficacy of using air‐fluidised beds for toxic epidermal necrolysis patients. (30th March 2015) - Xia, Weidong; Mao, Cong; Luo, Xu; Xu, Jianjun; Chen, Xiaofeng; Lin, Cai
Abstract: Objectives: Toxic epidermal necrolysis (TEN) is a potentially life‐threatening dermatological disease involving large areas of skin loss with systemic symptoms. This study evaluated the efficacy of air‐fluidised bed therapy for TEN patients. Methods: Of 27 people with TEN, 11 used air‐fluidised beds (the air‐fluidised group) and 16 used standard beds (the control group). Days to complete re‐epithelialisation, re‐epithelialisation rate, incidence of complications, mortality, pain measured by visual analogue score and the incidence of cutaneous infection were compared in these groups. Results: The mean body surface area of involvement was 77.0 ± 11.8% and baseline mean severity‐of‐illness score for TEN (SCORTEN) was 2.81 ± 1.08. The re‐epithelialisation rate in the air‐fluidised group was 100% but was only 56.3% in the control group ( P < 0.05). There was a significant difference in the time taken to complete re‐epithelialisation between the air‐fluidised group (13 days [95% CI: 9.0–17.0]) and the control group (21 days [16.5–25.5], P < 0.05). Furthermore, the incidence of complications was 18% in the air‐fluidised group versus 75% in the control group, including fewer cutaneous infections ( P < 0.05). There was a significant reduction in pain among the air‐fluidised group compared with the control group ( P < 0.05). There were no deaths in the air‐fluidised group while 19% of the control group died. Conclusion: Air‐fluidised beds can reduce the time to complete re‐epithelialisation, relieve pain and increase the re‐epithelialisation rate of TEN patients, but there was no significant difference between them in mortality rate in our study.